Opportunistic Termination - Alexander Stremitzer (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2008)
If a seller delivers a good non-conforming to contract, European and US warranty law allows consumers to choose between some money transfer and termination. Termination rights are, however, widely criticized, mainly for fear that the buyer may use non-conformity as a pretext for getting rid of a contract he no longer wants. We show that this possibility of 'opportunistic termination' might actually have positive effects. Under some circumstances, it will lead to redistribution in favour of the buyer without any loss of efficiency. Moreover, by curbing the monopoly power of the seller, a regime involving termination might increase welfare by enabling a more efficient output level in a setting with multiple buyers.
urn:nbn:de:bvb:19-epub-13326-0
Keywords: K12; C7; L40; D30; 330; contract law; warranties; breach remedies; termination; harmonization